Histology and Architecture: Parallel Worlds - Peña-Amaro, Jose (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2022)
In this article, the author raises the parallelism between two branches of knowledge: architecture and histology; from the consideration of the human body as a building. It tackles the use of architectural terms in the teaching of the microscopic structure of the human body, the equivalence between structures and constructive elements with cells, and the extracellular matrix. And finally, the similarities between the time-related stages of a building and those affecting the human body.